ROLE OF AGNIKARMA WITH ELECTRIC CAUTERY IN CHARMAKILA W. S. R. TO WART- A CASE DISCUSSION - V. Shekokar, Anantkumar; Borkar, Kanchan M. (International Journal of Ayurveda and Pharma Research, 2015)
Agnikarma Chikitsa was at peak level in Sushruta period but its use was declined gradually in modern era due to lack of availability of instruments and also the therapy was not easily acceptable by patient so in the present case study discussion we have made attempt on the disease Charmakila with the help of electric cauterization which is nothing but advanced version of ancient Agnikarma therapy. In present case study observation, efficacy of electric cauterization therapy shows minimum invasive parasurgical method in Charmakila (wart). One patient was treated on OPD basis in a minor OT of Ayurved college hospital Rahuri. Treatment was well tolerated by patient without complication during the therapy and post operative period. Hence, use of electric cautery as an Agnikarmas Dahanaupakarana in Charmakila is a best option with minimum trauma, easily acceptable by patient and surgeon in their fast day-to-day life.